Validity Of Overtime Beyond The Established Regulations Based On Employment Agreement At PT TKB - Tasya Destinasari; Ikram, Denial (Indonesian Journal of Labour Law and Industrial Relations, 2024)
This study examines the implementation of overtime work policies at PT TKB, a Food and Beverage company operating in Surabaya, with a focus on the "Store Keeper" position. The issue arises as the company imposes a 12-hour daily work schedule or 72 hours per week, as agreed upon in the employment contract, without providing overtime pay. This policy is based on the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia Number Kep.102/MEN/VI/2004, which exempts workers with certain responsibilities from receiving overtime wages. However, this raises questions regarding compliance with labor laws, particularly Law Number 6 of 2023. The study aims to analyze whether PT TKB's work-hour implementation aligns with applicable labor regulations and how legal protection is provided to workers under agreements that exceed standard work-hour provisions. The results of this research are expected to provide guidance for relevant stakeholders in ensuring that company policies comply with labor laws while enhancing the welfare and protection of workers' rights.